A state of the science on influential factors related to sun protective behaviors to prevent skin cancer in adults - Amy F. Bruce, MSN, RN, NE-BC; Laurie Theeke, PhD, FNP-BC; Jennifer Mallow, PhD, FNP-BC (Elsevier, 2017)
Skin cancer rates have risen over the past decades, making it imperative that adults understand the need for protection from sun exposure. Though some risk factors have been identified as predictive for skin cancers, there is a lack of synthesized information about factors that influence adults in their decisions to engage in sun protective behaviors. The purpose of this paper is to present the current state of the science on influential factors for sun protective behaviors in the general adult population. A rigorous literature search inclusive of a generally White, Caucasian, and non-Hispanic adult population was performed, and screening yielded 18 quantitative studies for inclusion in this review. Findings indicate that modifiable and non-modifiable factors are interdependent and play a role in sun protective behaviors. This study resulted in a proposed conceptual model for affecting behavioral change in sun protection including the following factors: personal characteristics, cognitive factors, family dynamics, and social/peer group influences. These factors are introduced to propose tailored nursing interventions that would change current sun protective behavior practice. Key implications for nursing research and practice focus on feasibility of annual skin cancer screening facilitated by advanced practice nurses, incorporating the identified influential factors to reduce skin cancer risk and unnecessary sun exposure.